2011
DOI: 10.1212/wnl.0b013e31821527f0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term intellectual outcome after temporal lobe surgery in childhood

Abstract: Objective: Temporal lobe resection is an established treatment for medication-resistant temporal lobe epilepsy, which in recent years has increasingly been performed in children. However, little is known about the long-term outcome in these children. The aim of this study was to characterize intellectual and psychosocial functioning of children after temporal lobe resection as they progress into late adolescence and adulthood. Methods:We report the long-term follow-up of 42 children who underwent temporal lobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
210
5
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(243 citation statements)
references
References 40 publications
24
210
5
4
Order By: Relevance
“…AEDs can have an impact on cognitive function with certain ones having an especially high risk. 28,29 Phenobarbital has residual effects even after discontinuation in young children treated for febrile seizures. 30 In utero exposure to certain AEDs, most notably sodium valproate, is associated with substantial decrements in cognitive function in early childhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AEDs can have an impact on cognitive function with certain ones having an especially high risk. 28,29 Phenobarbital has residual effects even after discontinuation in young children treated for febrile seizures. 30 In utero exposure to certain AEDs, most notably sodium valproate, is associated with substantial decrements in cognitive function in early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Further, surgical series also report some improvement in cognitive scores after surgery, suggesting that the seizures themselves negatively affect cognition and that the earlier the surgery is done, the better the postsurgical ability to acquire developmental and cognitive skills. 2,20,28,32 The hazards associated with seizures-injuries, mortality, and loss of autonomy-are all extremely important. Our data add to a building body of literature that highlights the cognitive consequences of poorly controlled seizures in the developing brain and provides more support for emerging recommendations and guidelines regarding early identification of pharmacoresistance 11 and referral to specialty care, particularly for children, 21 although similar considerations also occur in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Age range samples include patients less than 6 or 7 years at surgery, 19,28 3 to 7 years, 6 8 to 159 months, 34 less than 3 years, 20,26 or 3 to 36 months. 3 A number of studies 7,21,22,29,32,37 have focused on temporal lobectomies and have provided important information regarding outcome following this procedure, with some variable findings. Yet, these studies, so far, have wide surgical age ranges, crossing developmental stages, as well as lengthy presurgical seizure durations, lasting many years, and do not differentiate between outcome following short versus long presurgical seizure duration.…”
mentioning
confidence: 99%
“…56 Studies in epilepsy surgery patients have demonstrated that AED withdrawal achieves incremental IQ gains. [58][59][60] In a recent, randomised, placebo-controlled, phase II, double-blind study in adolescents with uncontrolled focal-onset seizures (n=133), no statistically significant difference was reported for add-on perampanel versus placebo in Cognitive Drug Research global cognition score. 61 In this study, perampanel was increased weekly in 2-mg increments to 8-12 mg/day during 6-week titration and the maintenance phase lasted 13 weeks.…”
Section: Impact On Behavioural Change In Epilepsymentioning
confidence: 99%